Checks and balances the three branches of the American government - Brannen, Daniel E. 1968-; Baker, Lawrence W.; Gale Group (Detroit, Mich. UXL, 2005)
Presents easy to understand information about the inner workings of the federal government. Includes historical overviews and examinations of the day-to-day operations of each branch, as well as Constitutional duties and obligations of each branch, specifics related to eligibility, elections and appointments of key positions, changes since 1776, the future of each branch, and other topics. For student and general audiences.
v.1. Executive -- v.2. Legislative -- v.3. Judicial.
Electronic reproduction.
Keywords: Electronic books; United States -- Politics and government